Mixed Methods and Multisited Migration Research: Innovations From a Transnational Perspective. (October 2018) - Fauser, Margit
This article discusses the use of mixed methods design for transnational migration research. It draws on two currently expanding strategies that can form part of an integrated framework that reveals multiple complementary perspectives: (a) the incorporation of quantitative data and methods in what has been a largely qualitative field and (b) the use of multisited research that investigates individuals and families connected across borders. This framework can be supported by collaboration of researchers across methodologies and state borders, which is addressed as a third strategy. By drawing on one research project that investigates the role of transnationality in the reproduction of social inequalities, this article explores the benefits and challenges of this approach.